Leveraging Virtual Reality Experiences to Shape Tourists’ Behavioral Intentions: The Mediating Roles of Enjoyment and Immersion - Sinh Hoang Nguyen (Journal of Zoological and Botanical Gardens)
This study investigates how virtual reality (VR) experiences influence tourists’ intentions to visit Da Lat, Vietnam, as a botanical destination, emphasizing the mediating roles of enjoyment and immersion. By integrating flow theory with the Information Systems Success model, this research develops a comprehensive framework explaining how content quality, system quality, and VR vividness shape user engagement and travel intentions. Using Structural Equation Modeling (SEM), the study analyzes survey data from 231 valid responses out of 240 participants. The findings reveal that content quality, system quality, and vividness significantly enhance enjoyment and immersion, which subsequently have a positive impact on travel intentions. The study contributes to the tourism and consumer experience literature by demonstrating how multisensory engagement in VR fosters decision-making. Theoretical implications include extending flow theory within virtual tourism and highlighting the joint influence of technological and perceptual factors on user behavior. Practically, these insights inform tourism marketers on optimizing VR environments to evoke emotional engagement and enhance destination appeal through immersive technology.